2018
DOI: 10.1002/clc.23118
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrical impedance analysis of body composition and survival in patients with heart failure

Abstract: Background: Studies have shown that higher body mass index (BMI) is associated with improved prognosis in heart failure (HF), and this is often termed the obesity paradox.Hypothesis: Analysis of body composition may reveal that muscle mass rather than adipose tissue accounts for the obesity paradox.Methods: Bioelectrical impedance analysis of body composition in 359 outpatients with HF was performed using an In Body 520 body composition scale (Biospace Inc., California). Body fat and lean mass were indexed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 37 publications
4
36
1
Order By: Relevance
“…10 Although BMI is high, this protective effect of overweight/obesity in these patients may be abolished in the presence of decreased lean mass and increased fat mass. 10,11 Moreover, increases in BMI cannot detect the regional body fat mass distribution, especially visceral fat that has been associated with mortality in these patients. 22 Furthermore, the protective effect of higher BMI should be considered with markers of functional capacity, once the obesity paradox has been described to be more significant in patients with lower cardiorespiratory fitness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Although BMI is high, this protective effect of overweight/obesity in these patients may be abolished in the presence of decreased lean mass and increased fat mass. 10,11 Moreover, increases in BMI cannot detect the regional body fat mass distribution, especially visceral fat that has been associated with mortality in these patients. 22 Furthermore, the protective effect of higher BMI should be considered with markers of functional capacity, once the obesity paradox has been described to be more significant in patients with lower cardiorespiratory fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Paradoxically, although obesity increases the risk of HF, obese patients with HF with reduced ejection fraction (HFrEF) may have lower mortality rate than patients with healthy standard body mass index (BMI; 18.5–24.99 kg/m 2 ) . However, the protective effect of higher BMI is abolished in the presence of reduced lean mass and increased fat mass …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BIA has been applied for the water management of hemodialysis patients and also recently for the water management of heart failure and cardiac surgery patients [16][17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…According to several reports on BIA in clinical studies, the phase angle (PA), one type of BIA readout, shared a correlation with a nutrition marker and was a potential postoperative risk marker for cardiac surgery [12][13][14][15]. Studies on the differences in water behavior with some kinds of diuretics found that one readout of BIA, the edema index (EI), being the ratio of extracellular water to total body water, can predict the amount of fluid reduction needed for patients with acute heart failure and chronic renal disease [16][17][18][19][20][21][22]. We hypothesized that perioperative water management could be improved by a better understanding of perioperative water behavior through BIA.…”
Section: Introductionmentioning
confidence: 99%